Applying Marketing Strategies of Chinese Online Platform Yuanfudao to Enter International Markets in a Pandemic - Fang Zhan; Denis Paleev (Communications of International Proceedings, 2021)
Online education is one of the fastest growing industries in China today. The market for investment in Chinese educational companies has outgrown the US market for several years. In 2015, the number of online education users in China was 110 million, with a market value of 114 billion yuan ($ 16 billion). Online learning has grown in popularity during the pandemic. This is confirmed by the rapid growth in the number of students and their activity on the platforms with online courses. In this, the number of online students grew by 63% to 179 million people, and the market value was 270 billion yuan ($ 41 billion). At the same time, the total global market for online education worldwide in 2019 amounted to $ 190 billion. This trend is expected to continue in the future. The whole world went online. According to UBS estimates, the market will grow to 714 billion yuan ($ 102.3 billion) by 2025 [1].
Keywords: Marketing; Marketing Strategy; Pandemic; Online Platforms; Promotion; Social Media; Brand.